Pax2a is expressed in oocytes and is responsible for early development and oogenesis in zebrafish - Pachoensuk, Theeranukul; Fukuyo, Taketo; Wanlada, Klangnurak; Rezanujjaman, Md; Rahaman, Md Mostafizur; Sasaoka, Kagura; Sarwar Jyoti, Md Maisum; Rana, Md Rubel; Ali, Md Hasan; Tokumoto, Toshinobu (My University, 2020)
Eleven genes, including pax2a, were selected as candidate ovulation-inducing genes on the basis of microarray analysis and RNA sequencing in our previous study. The purpose of this study was to investigate the role of the pax2a gene in the ovulation-inducing process. F2 pax2a homozygous mutant zebrafish possessing a deletion of 6 nucleotides were established in this study. However, the deletion included the start codon (ATG) of the pax2a gene, and the Pax2a protein was still detected, which indicated that the deletion caused a shift in the start codon to the next ATG, resulting in a 12-amino acid deletion. F2 pax2a homozygous mutant zebrafish showed ovulation. However, the embryos showed an abnormal oval shape at the epiboly stage that resulted in yolk and tail formation abnormalities and heart edema. The surviving F3 homozygous mutants did not develop ovaries. Pax2a was detected in oocytes and eggs but not after the Prim-22 stage. It is suggested that pax2a is expressed as a maternal gene in oocytes and is necessary for oogenesis and early development.
Keywords: Early development; Genome editing; Oogenesis; Ovulation; pax2a; Zebrafish